The exhaustion of the dollar : - Gray, H. Peter (Palgrave Macmillan, 2004)
The US dollar has served as the key currency of the international economic/financial system for over fifty years. This study assesses the proposition that the series of US current-account deficits over the last twenty years will shortly exhaust the capability of the dollar to continue as the key currency. The evidence in support of the proposition is strong. The implications of exhaustion will be serious and need to be addressed quickly.